An investigation on quantitative analysis of energy consumption and carbon footprint in the grinding process. (June 2014) - Ding, Hui; Guo, Dengyue; Cheng, Kai; Cui, Qi
The research presented in this article aims at developing an innovative integrated modelling methodology to quantify the energy consumption and equivalent carbon footprint in the grinding process. This article categorizes the energy consumption in four compositional parts and identifies the associated key factors affecting the energy consumption and equivalent carbon dioxide emission during the grinding process. Considering energy consumption (E), resource utilization (R), waste generation (W) and their collective effect on equivalent carbon dioxide (C) emission (ERWC), quantitative analysis modelling of the entire grinding process is developed against the roughing, finishing and spark-out stages of the process. The modelling and simulation analysis are carried out with the MATLAB environment, supported by the evaluation and validation through well-designed grinding trials.